2022
DOI: 10.1002/er.7957
|View full text |Cite
|
Sign up to set email alerts
|

A review on battery thermal management and its digital improvement‐based cyber hierarchy and interactional network

Abstract: The temperature has a significant influence on the performance of lithium-ion batteries (LiBs). Meanwhile, the heat-generated accumulation in the battery can trigger the battery's thermal runaway. Hence, the battery thermal management system (BTMS) is essential to ensure the safe and reliable operation of the battery. This paper comprehensively reviewed key technologies of BTMS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 168 publications
0
2
0
Order By: Relevance
“…Several investigations have shown that these components contain heat. Battery temperatures below 40 • C have been reported in references [34][35][36][37][38][39][40][41]. Meanwhile, studies such as [42][43][44][45][46][47][48][49] measured temperatures ranging from 40 • C to 60 • C, with [50,51] recording temperatures higher than 60 • C. Temperature changes in electric motors can be classified into three groups: less than 50 • C, as seen in [52], between 50 • C and 100 • C, as seen in [53][54][55][56][57][58][59] and above 100 • C, as seen in [60][61][62][63][64][65].…”
Section: Electric Motor and Batterymentioning
confidence: 99%
“…Several investigations have shown that these components contain heat. Battery temperatures below 40 • C have been reported in references [34][35][36][37][38][39][40][41]. Meanwhile, studies such as [42][43][44][45][46][47][48][49] measured temperatures ranging from 40 • C to 60 • C, with [50,51] recording temperatures higher than 60 • C. Temperature changes in electric motors can be classified into three groups: less than 50 • C, as seen in [52], between 50 • C and 100 • C, as seen in [53][54][55][56][57][58][59] and above 100 • C, as seen in [60][61][62][63][64][65].…”
Section: Electric Motor and Batterymentioning
confidence: 99%
“…Several investigations have shown that these components contain heat. Battery temperatures below 40°C have been reported in references [29][30][31][32][33][34][35][36]. Meanwhile, studies such as [37][38][39][40][41][42][43][44] measured temperatures ranging from 40°C to 60°C, with [45] and [46] recording temperatures higher than 60°C.…”
Section: Electric Motor and Batterymentioning
confidence: 99%